Reliability improvement of radial distribution system by optimization of sectionalizing device location using integer programming - Escobia, Jaime M. (2007)
Today there is a growing concern among electric utilities to improve the reliability of distribution systems. One of the ways to improve the reliability of a given distribution system is to optimize the placement or location of sectionalizing devices. Sectionalizing devices are used in primary distribution systems for various applications such as isolating or limiting faults, reconfiguring a given distribution network, and improving reliability. The costs associated with the installation of sectionalizing devices are quite significant. Therefore, a distribution system designer must be very careful in deciding how many and where sectionalizing devices are to be installed in a given circuit. The number and placement of sectionalizing devices in a radial distribution system depend on many factors, such as the type of customers connected, load variations, reliability considerations, and maintenance costs. Given the actual circuit average load for every segment of the two test circuits, the load-based reliability indices are computed using assumed repair rate and failure rate values. And by mathematical formulation using integer linear programming the type and location of sectionalizing devices are determined. Two distribution circuits from south area of Meralco namely, Balibago 42XV and Tanza 38ZW are selected as test circuits. Balibago 42XV is a mixed residential, commercial, and industrial circuit while Tanza 38ZW is a purely residential circuit. Integer Programming technique is used to solve the optimization of sectionalizing devices location problem with the help of the Optimization Solver from Microsoft Excel. The accuracy of the results of this study is validated by comparing them with the manual computation prepared by the author based on the book of R.Billinton [10]. The final result of the simulation shows that in general, selection of proper location, type, and number of sectionalizing devices in a distribution circuit would greatly enhanced their effectiveness in improving the reliability performance of a circuit.